The incidence of metabolic syndrome in psoriasis patients and its correlation with disease activity: a systematic review and meta-analysis - Li, Zongyang; Gu, Zheng; Xiang, Jingyu; Zhang, Xiaoyan (Frontiers in Medicine, 2025)
ObjectiveTo explore the association between psoriasis and metabolic syndrome (MetS) and analyze the impact of disease activity on the risk of MetS occurrence.MethodThis systematic review and meta-analysis used computer searches to search for relevant literature on psoriasis and MetS in databases including China National Knowledge Infrastructure (CNKI), PubMed, Web of Science, Cochrane Central Register of Controlled Trials (CENTRAL) and Embase. The search period was from the establishment of the database to February 8, 2025. Inclusion in case–control, cohort studies and cross-sectional, with language restrictions in Chinese and English during retrieval. After independent screening of literature, extraction of data, and evaluation of risk bias for inclusion in the study by two evaluators, meta-analysis and subgroup analysis were conducted using Stata17.0 software.ResultA total of 12 studies were analyzed, encompassing 9,641 patients with psoriasis and 2,554 patients suffering from MetS alongside psoriasis. The incidence of metabolic syndrome in psoriasis patients was analyzed and the combined effect size was 26.49% [95% CI (25.61, 27.39%)]. Results from the meta-analysis indicated that, in comparison to the control group, psoriasis patients demonstrated a heightened risk of developing MetS [OR = 1.27, 95% CI (1.21–1.33), p < 0.001]. Subgroup analysis revealed that patients with severe psoriasis (PASI≥10) had a significantly increased risk of developing metabolic syndrome [OR = 2.25 95% CI (1.27, 3.99), p < 0.001], indicating that greater disease activity is associated with an elevated likelihood of MetS occurrence.ConclusionPsoriasis is positively correlated with MetS risk, and increased disease activity further increases the risk. It is necessary to strengthen screening for metabolic abnormalities and multidisciplinary management.